Static repair of multiple cracked beam using piezoelectric patches - Hai, Tran Thanh (Vietnam Journal of Mechanics, 2021)
This paper addresses the problem of repairing multiple cracked beams subjected to static load using piezoelectric patches. First, the problem is formulated and solved analytically for the case of two cracks that results in ratio of restoring moments produced by employed piezoelectric patches. Since the ratio is dependent only on crack positions but not their depth, the result obtained for case of two cracks has been extended for the case of multiple cracks. This proposition is then validated by finite element simulation where repairing piezoelectric patches are replaced by mechanical moment load equivalent to the restoring bending moments produced by the piezoelectric patches. The excellent agreement between analytical solution and numerical simulation results in case of single and double cracks allows making a conclusion that a piezoelectric patch could productively repair a cracked beam by producing a restoring moment due to its piezoelectricity. Thus, the problem of repairing multiple cracked beam using piezoelectric patches is solved.